Faktor-faktor yang Mempengaruhi Kesehatan Mental Mahasiswa Bimbingan dan Penyuluhan Islam UIN Syarif Hidayatullah Jakarta - Bella Salsa Risnawati; Nasichah Nasichah; Muhammad Faqih Prayogo; Zannuby Al Izzami (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Currently, mental health issues are a widely discussed topic. Cases related to mental health began to appear in the community, about 20% of the population in Indonesia has the potential for mental health problems. Mental health disorders also occur in college students, this is indicated by the number of suicides in students. This study was conducted to determine the factors experienced by students and influence mental health. The method used is descriptive statistics with univariate analysis. The results showed that students' mental health was more influenced by psychological factors, with a percentage of 65,1%.